Perceived Implication of Cyber Relational Addiction on Young Adults Social Well-Being in Ogun State, Nigeria - ADENUGA, Emmanuel; Adeola Oladele OGUNSANYA (African Journal of Behavioural and Scale Development Research, 2025)
This study assessed the implications of cyber relational addiction on social well-being of young adults in the study location. The study used descriptive survey design and a sample size of five hundred young adults selected through convenience sampling techniques. The instrument used for the study was a self-structured questionnaire with reliability index of 0.85. Data obtained were analyzed with the aid of Statistical Package for Social Science, using frequency count, percentage and mean to answer the research questions. Results from the study showed that the CRA exists among 62.2% female and 79% among age 21 - 25 years, and there was a slight difference in the magnitude based on educational level with 46.2% Secondary and 53.8% post-secondary education. The mean range of the implication on Social Well-Being Aspects 2.51 (0.110) to 3.55 (0.250) is significant. The finding was that CRA negative implications outweigh its positive effects in the study location. Based on this, among the recommendations made was that schools and institutions should organize aggressive awareness campaign to educate students on the risks and negative impact of CRA on social well-being as well as encourage the young adults to balance online and offline relations.